Bioprinting salivary gland models and their regenerative applications - Jutapak Klangprapan; Glauco R. Souza; João N. Ferreira (Nature Publishing Group, 2024)
Abstract Objective Salivary gland (SG) hypofunction is a common clinical condition arising from radiotherapy to suppress head and neck cancers. The radiation often destroys the SG secretory acini, and glands are left with limited regenerative potential. Due to the complex architecture of SG acini and ducts, three-dimensional (3D) bioprinting platforms have emerged to spatially define these in vitro epithelial units and develop mini-organs or organoids for regeneration. Due to the limited body of evidence, this comprehensive review highlights the advantages and challenges of bioprinting platforms for SG regeneration. Methods SG microtissue engineering strategies such as magnetic 3D bioassembly of cells and microfluidic coaxial 3D bioprinting of cell-laden microfibers and microtubes have been proposed to replace the damaged acinar units, avoid the use of xenogeneic matrices (like Matrigel), and restore salivary flow. Results Replacing the SG damaged organ is challenging due to its complex architecture, which combines a ductal network with acinar epithelial units to facilitate a unidirectional flow of saliva. Our research group was the first to develop 3D bioassembly SG epithelial functional organoids with innervation to respond to both cholinergic and adrenergic stimulation. More recently, microtissue engineering using coaxial 3D bioprinting of hydrogel microfibers and microtubes could also supported the formation of viable epithelial units. Both bioprinting approaches could overcome the need for Matrigel by facilitating the assembly of adult stem cells, such as human dental pulp stem cells, and primary SG cells into micro-sized 3D constructs able to produce their own matrix and self-organize into micro-modular tissue clusters with lumenized areas. Furthermore, extracellular vesicle (EV) therapies from organoid-derived secretome were also designed and validated ex vivo for SG regeneration after radiation damage. Conclusion Magnetic 3D bioassembly and microfluidic coaxial bioprinting platforms have the potential to create SG mini-organs for regenerative applications via organoid transplantation or organoid-derived EV therapies.